Meclis-i Meşâyihin Bulaşıcı Hastalıklarla İlgili Aldığı Tedbirler - Aydınlı, Meliha (İstanbul Sabahattin Zaim Üniversitesi, 2024)
Tarih boyunca insanlığı etkileyen bulaşıcı hastalıklar, özellikle toplu yaşam alanların-da görülmekte ve insan hayatını olumsuz etkilemektedir. Salgınlar; Osmanlı Devle-ti’nin ictimaî yapısında önemli bir yer teşkil eden ve her kesimden insana ev sahipliğiyapan tekke ve zaviyelerde de tehdit edici bir unsur olarak gündeme gelmiştir. Şey-hülislamlık bünyesinde tesis edilen ve tekkelerin yönetimi ile denetiminden sorum-lu olan Meclis-i Meşâyih (1866-1925), bulaşıcı hastalıklarla ilgili birtakım tedbirleralmıştır. Bunlardan en önemlisi; tekkelerde dikkat edilmesi gereken durumlarla ilgiliMeclis’in yayınladığı talimatnamedir ve burada virüsler, hijyen ve temizlik ile dikkatedilmesi gereken hususlardan bahsedilmektedir. Talimatnamede; temizliğin İslam’ınşartı olduğu, sağlıklı yaşamın birinci kuralının nezafet dolu bir yaşamdan geçtiği, iç-timaî yaşam alanlarında bu tür hastalıklarla daha fazla karşılaşılabileceği belirtilmiş,kurallara uyulması ve konunun dikkate alınması tavsiye edilmiştir. Ayrıca Meşihatdairelerinde görevli memurlara aşı mecburiyeti getirilmiş ve karantina uygulamasıyapılmıştır. Bu makalede, Meclis-i Meşâyihin bulaşıcı hastalıklarla ilgili yayınladığıtalimatname ile Meşihat dairesinde alınan tedbirler ve konuyla ilgili Meclis-i Meşâyihdefterlerinde ele alınan kararlar incelenecektir.

Infectious Infectious diseases, which have affected humanity throughout history, areespecially seen in collective living spaces and negatively affect human life. Epidemicswere also a threatening factor in tekkes and zawiyahs, which played an importantrole in the social structure of the Ottoman Empire and hosted people from all walksof life. The Meclis-i Meşâyih (1866-1925), which was established within the body ofthe Şeyhülislam and was responsible for the management and supervision of tekkes,took a number of measures against infectious diseases. The most important of thesewas the directive issued by the Assembly on the conditions to be taken into conside-ration in tekkes, where viruses, hygiene, cleanliness and issues to be considered arementioned. In the directive, it was stated that cleanliness was a pillar of Islam, thatthe first rule of a healthy life was a life full of decency, that such diseases were morelikely to be encountered in social living spaces, and it was recommended that the rulesbe followed and the issue be taken into consideration. In addition, vaccination wasmade compulsory for officials working in the offices of the Meşihat and quarantinepractices was imposed. This article examines the instructions issued by the Meclis-iMeşâyih on infectious diseases, the measures taken in the office of the Mashihat, andthe decisions taken in the books of the Meclis-i Meşâyih in this subject.
Meclis-i Meşâyih’s Precautions About Epidemic Diseases
Keywords: Meclis-i Meşâyih; Bulaşıcı hastalıklar; Talimatname; Karantina; Aşı; Meclis-i Meşâyih; Infectious diseases; Instruction; Quarantine; Vaccination